Gestão do capital de giro: o Vendor como fonte de recurso para suprir necessidades de caixa para a pequena empresa - Oliveira, Wilson Lourenço de (2019)
Operating in unstable markets, with high tax burden and limitations on access to credit lines, mainly aimed at MSEs, makes industrial companies, suppliers of goods and distributors, generally, act to grant installment to expand sales of their products. . When the term sale is granted, the financial costs are usually applied to the price of the asset, increasing the amount of taxes payable, since it increases the calculation base, final sale value, when issuing the invoice. These costs could be reduced through the use of the Vendor credit product, which enables the issuance of the sales invoice, in the case of installments, in its cash sale price, resulting in a reduction in the amount of taxes. sales and commission expenses to sellers and royalties or manufacturing license. And, in the case of advance of credit securities (with the issuance of trade notes) through financial institutions, interest rate costs may be lower than the interest rates charged on the trade discount product. This product, the Vendor, was made available to the market since the 1980s and, even with the advantages promoted by the product, there are few operations in the credit market, according to the evidence presented by the Central Bank of Brazil, which shows the participation 6.24% of the product of discount of duplicates in the corporate credit market. Given the scenario presented, the general objective of this dissertation was to disseminate the purpose and advantages of the Vendor product over the duplicate discount product, sovereign in credit operations statistics. To achieve the proposed objectives, a qualitative approach research was conducted, with literature review, through literature review and, in addition to the study, an exploratory research was conducted with cash management managers, located in branches of the city of São Paulo and metropolitan regions. The evaluation of the survey result, the description of the final considerations, concluded that, on the perception of cash management managers, the majority of small business owners / representatives most often negotiate the trade discount product aimed at address the need to anticipate working capital resources by negotiating the Vendor product less frequently